A Descriptive Study on Patterns of Traumatic Spinal Injuries in a Tertiary Care Hospital Rawalpindi - Fraz Mehmood, Fraz Mehmood; Yasir Shahzad, Yasir Shahzad; M. Motism Shah, M. Motism Shah; Nadeem Akhtar, Nadeem Akhtar; Fatima Hashmi, Fatima Hashmi; Danish Badar, Danish Badar (Journal of Rawalpindi Medical College, 2022)
Introduction: Spinal injuries are one of the most debilitating injuries if not fatal and affect every dimension of patients’ lives i.e. early mortality and late complications. Lifelong disability due to spinal cord injury is very common even if the patient survives early death. The current study was aimed to investigate the frequency, management, mortality, the pattern of spinal injuries and to recommend plans for better patient management based on assessment. Material and Methods: The study was descriptive, cross-sectional, and was conducted at the Neurosurgery Department of Rawalpindi Medical University and Allied Hospitals for the duration of October 2018 to January 2019. All cases of traumatic spinal injuries were included and variables noted were gender, age, mode of Injury, presenting motor power in limbs, ASIA score, diagnosis, management, outcome, and deaths. Results: In the sample size of 84 patients, the mean age was 37.1 years, the mechanism of injury due to falls was most common at 73%, the lumbar region was found to be the most common area involved. Male patients outnumbered females in the study. 14% of the patients could not survive due to the injury, 15% received cervical traction, 4% received cervical traction and anterior cervical plating, and 43% of patients underwent Transpedicular Screw Fixation, the total number of patients who expired was 25%. Conclusion: Patterns of traumatic spinal injuries are changing, shifting from road traffic accidents to falls being the primary cause nowadays, with prolonged hospital stay periods, disability for life, and high-cost treatments putting a huge burden on our already exhausted health resources. Efforts should be made to make a national registry for traumatic spinal injuries presented to the emergency department and guidelines should be established regarding occupational hazards. Awareness should be given to the general population regarding hazards at home regarding falls.